Frequency of Atrial Fibrillation in Patients of Hypertension - Tariq, Muhammad Naeem; Rashid, Muhammad Humayoun; Chaudhery, Ghoza; Komel, Aqsa; Aisha, Azka; Usman, Ahmad; Yaseen, Ghulam (Cardiology and Cardiovascular Medicine, 2021)
Background: Hypertension is a major cause of premature vascular disease leading to cerebrovascular events, ischemic heart disease and peripheral vascular disease. Hypertension and heart failure are most often associated with atrial fibrillation (AF). It together with hypertension proves to be fatal as it leads to stroke and cardiovascular events. Objective: To determine the frequency of AF in patients of hypertension. Material and methods: It is a cross-sectional study done in Punjab Institute of Cardiology, Lahore and CPE Institute of Cardiology Multan during a duration of six months from 07/02/2020 to 07/08/2020. Data collection: Patients with BP>140/90 mmHg were included. Later on, ECG was taken on a standard 12 lead format. Presence of AF was confirmed. All the data was recorded in a pre-structured proforma. Results: The mean age of the patients was 48.64 ± 7.74 years. Majority of the cases 148 (74%) were male while 52 (26%) were female. AF was noted in 22 (11%) of cases. AF was significantly higher in patients above 40 years of age (P<0.05) while gender difference and duration of hypertension has insignificant effect on AF (P>0.05). Conclusion: The frequency of AF is low in hypertensive patients but the value is not ignorable. Periodical screening of AF is required to prevent hazardous consequences.